Is there a relationship between periodontitis and rheumatoid arthritis? - Sarika Bhalgat Ranade; Satish Doiphode (Wolters Kluwer Medknow Publications, 2012)
Background: Growth of scientific evidence suggests an exquisite association between oral infection and systemic diseases. Though etiologies of periodontitis and rheumatoid arthritis (RA) are separate, their underlying pathological processes are sufficient to warrant consideration of hypothesis that individuals at risk of developing RA may also be at the risk of developing periodontitis and vice versa. Materials and Methods: To test their relationship, a study was carried out on 80 individuals. Part A: Forty subjects having rheumatoid arthritis (RA group) were compared to 40 controls without arthritis (NRA group). Their periodontal indices rheumatoid arthritis clinical laboratory parameters were also correlated with periodontitis in group. Part B: Omplete periodontal treatment was done for 10 patients of group suffering from periodontitis. All parameters of periodontal indices were measured pre-operatively and weeks after completion of periodontal treatment. Results: (1) There was high prevalence of mild (12.5%) to moderate (75%) periodontitis in group. (2) Extent severity of periodontal disease rheumatoid arthritis were positively correlated. (3) Statistically significant differences were present in periodontal parameters of RA group compared to NRA group. (4) There was statistically, significant reduction in parameters postoperatively with concomitant decrease in periodontal parameters in RA group. Conclusion: Thus, an association exists between periodontal disease with an underlying dysregulation of the molecular pathways in the inflammatory response. Also, there are significant management implications in the future as new host modifying medications are developed.